Conceptual framework for effective E-collaboration and didactic enhancement - Yussiff, A.-S. (Institute of Electrical and Electronics Engineers Inc., 2014)
E-collaboration environment through social media technologies is a promising pedagogical approach for teaching, learning and research. It will support student-to-student, student-to-lecturer, and student-to-content interaction and collaboration in a higher educational institution. Despite these benefits, many educators are still reluctant to start experimenting or using it. Drawing on current developments in social media software, a literature review on online collaborative teaching and learning, theories of learning, basic concepts, as well as action research using social media technologies, this paper reviewed and described eight existing frameworks for e-collaboration and five learning theories using nine and four criteria respectively. Following an analysis of the frameworks and learning theories, a conceptual framework for effective e-collaboration and the didactic enhancement is proposed for higher educational institutions with support for planning, design, development, implementation and evaluation of such an environment. The findings, conclusions and implications for future research in this area are further provided. Â© 2014 IEEE.